2022
DOI: 10.1002/ecm.1527
|View full text |Cite
|
Sign up to set email alerts
|

Accidental epiphytes: Ecological insights and evolutionary implications

Abstract: Vascular epiphytes are an important component of many ecosystems and constitute a substantial part of global plant diversity. In this context, accidental epiphytism, that is, the opportunistic epiphytic growth of typically terrestrial species, deserves special attention because it provides crucial insights into the global distribution of vascular epiphytes and the initial evolution of epiphytic lineages. Even though accidental epiphytes have been mentioned in the literature for more than a century, they have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 203 publications
0
9
0
Order By: Relevance
“…Such individuals are called "accidental epiphytes", and have traditionally been treated as a curiosity that does not merit much attention. Recently, Hoeber and Zotz (2022) reviewed the available information on accidental epiphytes and developed a framework for the scientific exploitation of this phenomenon. They argued that ignoring accidental epiphytism has been a lost research opportunity, because their study should provide crucial insights into the initial evolution of epiphytic lineages and give important context for a mechanistic understanding of the global distribution of vascular epiphytes in general.…”
Section: Notementioning
confidence: 99%
“…Such individuals are called "accidental epiphytes", and have traditionally been treated as a curiosity that does not merit much attention. Recently, Hoeber and Zotz (2022) reviewed the available information on accidental epiphytes and developed a framework for the scientific exploitation of this phenomenon. They argued that ignoring accidental epiphytism has been a lost research opportunity, because their study should provide crucial insights into the initial evolution of epiphytic lineages and give important context for a mechanistic understanding of the global distribution of vascular epiphytes in general.…”
Section: Notementioning
confidence: 99%
“…Another major problem with the application of categories is related to intraspecific variability. As discussed for accidental epiphytes (Hoeber et al, 2019;Hoeber & Zotz, 2022), members of the same species can exhibit different growth forms, for example individuals of terrestrial species can sometimes be found growing epiphytically and normally terrestrial trees may develop as a hemiepiphyte. To capture this variation beyond the anecdotal level, F I G U R E 1 Conceptual graph of the different forms of climbers in Araceae are defined by the site of germination and the resulting ontogenetic changes in root and shoot contact (connections) with the soil.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike mistletoes, epiphytes are not parasitic, that is, they do not utilize water and nutrient supplies of the host itself (Zotz, 2016). While growth conditions for root systems of epiphytic plants in tree forks or in humus mats hardly differ from those of terrestrial plants on the forest floor (Hoeber & Zotz, 2022), growth on bare bark poses a suite of particular challenges. On bark, epiphytes cannot develop a deep root system for anchorage like their terrestrial ground‐rooted counterparts (Coutts, 1983; Ennos, 2000).…”
Section: Introductionmentioning
confidence: 99%